Complement activation, a threat to pregnancy - Girardi, Guillermina (Seminars in immunopathology, 2018)
Pregnancy poses a challenge for the immune systems of placental mammals. As fetal tissues are semi-allogeneic and alloantibodies that commonly develop in the mother, the fetus and the placenta might be subject to complement-mediated immune attack with the potential risk of adverse pregnancy outcomes. Here, I describe how the use of animal models was pivotal in demonstrating that complement inhibition at the fetomaternal interface is essential for a successful pregnancy. Studies in animals also helped the identification of uncontrolled complement activation as a crucial effector in the pathogenesis of recurrent miscarriages, intrauterine growth restriction, preeclampsia, and preterm birth. Clinical studies employing complement biomarkers in plasma and urine showed an association between dysregulation of the complement system and adverse pregnancy outcomes. A better understanding of the role of the complement system in pregnancy complications will allow a rational approach to manipulate its activation as a potential therapeutic strategy with the goal of protecting pregnancies and improving long-term outcomes for mother and child.